Examination of Bank-Specific and Macroeconomic Determinants of Islamic Banks Profitability in Bangladesh: A Panel Data Approach - Haque, Muhammad Enamul; Farzana, Nusrat (Asian Journal of Empirical Research, 2018)
Islamic banks have continued to demonstrate tremendous growth over the last decade as reflected by its increasing market shares in terms of deposits and investments compared to the total banking system. This study makes an effort to examine the bank-specific and macroeconomic determinants of eight full-fledged Islamic banks profitability in Bangladesh applying two static linear panel data approaches. The study uses return on assets, return on equity and net investment margin as measures of profitability. The results indicate that bank-specific variables such as capital to risk based assets, liquidity, bank size, and operating efficiency are highly correlated with Islamic banks profitability. Both the macroeconomic variables are found to be statistically nugatory and do not have any influence to affect the Islamic bank profitability.